The Sandstorm : The Arab-Israeli War of June, 1967 : Prelude and Aftermath - Kimche, David and Bawley, Dan (Lodon Secker & waburg, 1968)
A summary of the Six Days' War and of events leading up to it and immediately following it. Emphasis is on the politics and negotiations behind the war, not on battle tactics.
Includes Illustrations and Index
Keywords: Diplomatic History -- Israel-Arab War (1967)